Discourses of White Nationalism and Xenophobia in the United States and Their Effect on TESOL Professionals in Mexico. Issue 3 (12th August 2019) - Sayer, Peter; Martínez‐Prieto, David; Carvajal de la Cruz, Brenda
Abstract : White nationalism has emerged in the mainstream of U.S. political discourse, and restricting all forms of immigration has become a central focus of isolationist, "America First" policies. In August 2017, TESOL International released its Position Statement on Immigration Policy and Reform in the United States . The authors respond to the position statement and address Mexican English teachers' views towards the immigration debate in the United States, how this debate reflects what Mexicans see as discourses of White nationalism and xenophobia, and the impact they have on the everyday work that teachers do in English classrooms in Mexico. They begin by giving a brief historical background on the closely intertwined relationship between the two countries, and then discuss the effects of the current climate on language educators' work. They explain that manifestations of anti‐Mexican xenophobia in the United States increase the difficulty of Mexican English language educators as students of all ages are well aware of the rhetoric coming from the United States, and are increasingly translating these negative words and images into a negative sense of what it means to learn English. Three strategies are described that English teachers in Mexico often use within their classrooms to engage students in exploring the connection between English and the United States, harnessing the potential of the language classroom as a forum for naming, understanding, and contesting discourses that promote intolerance and racism.